2020
DOI: 10.3390/foods9040465
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Visual-Taste Congruency on Perceived Sweetness and Product Liking in Immersive VR

Abstract: This study was designed to assess whether the combined effect of taste-congruent and incongruent extrinsic visual cues presented in virtual reality (VR) influences the perception of sweetness and product liking. Three VR environments (sweet-congruent, sweet-incongruent, and neutral) were created based on the evidence in existing literature. Participants tasted the same beverage in three VR environments and evaluated the environment and beverage liking, as well as perceived taste intensity (sweetness, sourness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 79 publications
(102 reference statements)
2
36
0
Order By: Relevance
“…We could only calculate effect size for those studies where either t-values or the combination of means and standard deviation/error were reported. size tested (N = 32), although this is in line with previous VR and color studies [N = 50 per cell (study 1) and N = 25 per cell (study 2) in Ammann et al (2020); N = 41 in Chen et al (2020)]. Another demographic issue is the admittedly uneven gender distribution of mostly men, due to the fact that we collected a convenience sample from computer science courses.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We could only calculate effect size for those studies where either t-values or the combination of means and standard deviation/error were reported. size tested (N = 32), although this is in line with previous VR and color studies [N = 50 per cell (study 1) and N = 25 per cell (study 2) in Ammann et al (2020); N = 41 in Chen et al (2020)]. Another demographic issue is the admittedly uneven gender distribution of mostly men, due to the fact that we collected a convenience sample from computer science courses.…”
Section: Discussionsupporting
confidence: 76%
“…They demonstrated that seeing modified product colors in VR did in fact negatively impact flavor identification, and that flavor identification performance was not significantly different when participants did the study in VR vs. in real life, using food-coloring-modified products. Finally, even food-extrinsic changes in virtual environment have been shown to influence taste evaluations of different foods, such as a grenadine-based beverage tasting sweeter when consumed in a sweet-congruent environment compared to a bitter-congruent environment ( Chen et al, 2020 ), or when cold brew coffee tastes sweeter when consumed in an environment with pleasant color and music, compared to one with unpleasant color and music ( Nivedhan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the farm atmosphere, it is possible that a sensation transference effect was at play and predominant colors in the atmospheres influenced participants' tastes perception (Cheskin, 1957 ; Chen et al, 2018 ). Indeed, Chen et al ( 2020 ) found that sweet-congruent (i.e., round shapes and red colors) VR environments can increase the perception of sweetness of beverages (i.e., grenadine juice). In our case, it is possible that participants associated the high amount of green color with expectations of acidity of the coffee.…”
Section: Discussionmentioning
confidence: 99%
“…Given the possibilities VR brings to consumer contexts, there has been a growing number of articles on VR in sensory and consumer science in recent years (Spence et al, 2016 ; Sinesio et al, 2018 ; Stelick et al, 2018 ; Andersen et al, 2019 ; Hannum et al, 2019 ; Petit et al, 2019 ; Picket and Dando, 2019 ; Chen et al, 2020 ). VR is becoming an effective tool for companies to develop immersive brand experiences with the potential to transport consumers to specific locations an allow them to “live” stories (see also Rogers, 2018 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this Special Issue, Chen et al [ 9 ] dig deeper into how taste perception (sweetness) is perceived through sensory information coming from different senses. They use an immersive technology (Virtual Reality) to present visual cues to their participants to create a sense of immersion and feelings of presence and involvement.…”
mentioning
confidence: 99%